(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
The article reveals the process of development of English children’s literature in the 19th-20th centuries on a scientific and theoretical basis. The study examines the literary interpretation of the concept of childhood, the formation of the image of childhood as an independent aesthetic phenomenon in the era of Romanticism, as well as the emergence of the fantasy genre into a leading position in the 19th-20th century. Using the example of J.R.R. Tolkien, C.S. Lewis and J.K. Rowling. J. K. Rowling substantiates the importance of the fantasy genre in the formation of children’s thinking, moral values and aesthetic taste. The article reveals the role and importance of English children’s literature in the global literary process.